Parental divorce and nicotine addiction in Lebanese adolescents: the mediating role of child abuse and bullying victimization - Elie Bou Sanayeh; Katia Iskandar; Marie-Claude Fadous Khalife; Sahar Obeid; Souheil Hallit (BMC, 2022)
Abstract Background Lebanon ranks first amongst Middle-Eastern countries in terms of cigarette and waterpipe smoking. Understanding the mediating factors for nicotine addiction in adolescents who have experienced parental divorce is vital to take effective measures that will help in lowering its prevalence in our community. The objective of this study was to investigate the association between the increasingly concerning parental divorce and nicotine addiction in Lebanese adolescents while taking into consideration the plausible mediating effect of abuse and bullying victimization. Methods This was a cross-sectional survey-based study that was conducted between January and May 2019. A total of 1810 adolescents aged between 14 and 17 years was enrolled from 16 Lebanese schools. Linear regressions taking the cigarette and waterpipe dependence scores as dependent variables were conducted respectively, using the SPSS software. PROCESS v3.4 model 4 was used for mediation analysis. Results A total of 11.9% of the enrolled participants had divorced parents. Higher cigarette and waterpipe dependence were found in adolescents whose parents were divorced compared to those living together. More child psychological abuse, having divorced parents vs living together, and more child physical abuse were significantly associated with higher cigarette dependence. More child psychological and physical, and having divorced parents vs living together were significantly associated with more waterpipe dependence. In addition, all forms of abuse (except neglect) and bullying victimization had a partially mediating effect in the associations between parental divorce and nicotine dependence (cigarette and waterpipe) in adolescents. Conclusion This study results may serve as a first step towards enrolling separated parents and their children in special prevention programs to help them create a protective and supportive environment.